Perceptions of post vaccination Bacillus Calmette-Guérin scar formation among caregivers in tertiary health institution in North-East, Nigeria - Bulus, Solomon Gideon; Martins, Olutayo Folashade; Bulus, Wasinda Solomon; Hayatu, Ahmad; Abraham, Joshua Msonter (International Journal Of Community Medicine And Public Health, 2025)
Background: Tuberculosis continues to be one of the major causes of morbidity and a leading cause of mortality worldwide, especially in low- and middle-income countries like Nigeria. To effectively contribute to the fight against tuberculosis (TB), mothers must be well-informed about TB and how to prevent TB in children. The objective of this study was to evaluate the knowledge and perception of mothers about Bacillus Calmette-Guérin (BCG) scarring. Methods: This was a cross-sectional descriptive study performed from July to December 2024 in a tertiary health care facility in Yola, Nigeria. Results: Majority (80%) of the caregivers were aware that BCG protects against tuberculosis, about 95% believed BCG can result in scar formation and 61% agree that presence of scar indicates that BCG vaccine is working. About 90% of the caregivers would report to a health facility when the scar fails to appear after BCG vaccination. Conclusions: Majority of the caregivers (mothers) were found to be aware that BCG protects against TB and accept BCG scarring following vaccination. We recommend regular health education to mothers during routine immunization to maintain adequate and accurate health information on vaccines.